Bronchial artery embolization for the management of frequent hemoptysis caused by bronchiectasis - Guang-Dong Lu; Hai-Tao Yan; Jin-Xing Zhang; Sheng Liu; Hai-Bin Shi; Qing-Quan Zu (BMC Pulmonary Medicine, 2022)
Abstract Background To retrospectively evaluate the effectiveness of bronchial artery embolization (BAE) compared with conservative therapy for the treatment of frequent hemoptysis caused by bronchiectasis. Methods From January 2015 to December 2019, consecutive patients who were admitted due to frequent (more than three times per year) bronchiectasis-related hemoptysis were retrospectively reviewed. Those who were treated with either BAE (n = 69) or conservative therapy (n = 47) were enrolled for analysis. The technical success, clinical success, and complications of the BAE procedure were evaluated. Long-term hemoptysis-free survival rates and clinical success were compared between patients in the BAE group and patients in the conservative group. A Cox proportional hazard regression model was used to identify the predictors of recurrent hemoptysis. Results The technical success rate was 100% for the BAE procedure, and clinical success was achieved in 92.8% (64 of 69) of cases. No major procedure-related complications occurred, and minor complications were observed in 16 cases (23.2%). The 1-, 2-, and 3-year hemoptysis-free survival rates were 88.3, 71.3, and 66.2%, respectively, for the BAE group and 31.9, 17.6, and 2.5%, respectively, for the conservative treatment group (P <  0.001). Multivariate analysis showed that BAE was a protective factor against recurrent hemoptysis in treated patients. In addition, the presence of cystic bronchiectasis was the only independent risk factor for rebleeding in the whole population and in the BAE group. Conclusions BAE may provide an effective option for patients with frequent bronchiectasis-related hemoptysis, especially for those without cystic bronchiectasis.